Lean-Based Design and Analysis of a Continuous Improvement Engineering Approach for Jordanian Land Transport Industry - AL-Tahat, Mohammad D.; Mohammed, Mohammed Juma (International Journal of Membrane Science and Technology, 2023)
For an open, competitive, and lean economy, especially in industrialized development nations like Jordan, competitiveness, efficiency, and low global transportation costs are crucial. It is vital to address these concerns to sustain lean transportation services. This paper intends to present a lean-based analysis of a continuous improvement approach for Jordanian land transport industry, the aim behind that is to improve the overall effectiveness of the Jordanian land transportation sector. The research uses the Structural Equation Modelling (SEM) as a lean tool to fill the knowledge gap between theory and practice and to shed light on the continual improvements of Jordan's land transportation sector. Five of the largest land transportation companies have provided data, which has been gathered using primary and secondary data sources. Managers, drivers, and operations officers are polled using a 65-question Five-Point-Likert survey. The research looks at how the cost of transportation, customer satisfaction, safety, management emphasis, travel time, and driving abilities affect overall effectiveness. Operations, technical, and managerial efficiency are the metrics used to evaluate efficiency. Eight hypotheses between three efficiency measures and six independent variables are brought up. Correlations, tolerance tests, and Variance Inflation Factor (VIF) multicollinearity tests validate and confirm the findings. The research identifies significant barriers impeding the effectiveness of Jordan's land transportation industry and seeks to close the gap between theory and practice. Future research plans to investigate how other Jordanian service sectors measure their efficiency because the developed approach is useful and applicable.